Analysis of the Influence of the Use of Information Technology and Knowledge Management on Employee Performance with Motivation as an Intervening Variable (Studies in the Regional Government of Sidoarjo Regency) - Fita Fitria Lestariana; Sigit Hermawan (Proceedings of The ICECRS, 2021)
This study aims to determine and analyze the influence of Information Technology Utilization and Knowledge Management on Employee Performance with  Motivation as Intervening Variables in the Regional Government of Sidoarjo  Regency. The analytical tool used  in  the form of a  questionnaire distributed  to  100 employees in 15 sub-districts in Sidoarjo regency with the results of the use of Information Technology has a significant effect on motivation; knowledge management has a significant effect on motivation; the utilization of Information Technology and knowledge management simultaneously have a significant effect on motivation; Information Technology utilization has a significant effect on employee performance; knowledge management has a significant effect on employee performance; motivation has a significant effect on employee performance and the use of Information Technology and knowledge management has a direct and significant effect on employee performance through motivation.